2012
DOI: 10.1155/2012/729708
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic, Thermal, and Antimicrobial Studies of Co(II), Ni(II), Cu(II), and Zn(II) Complexes Derived from Bidentate Ligands Containing N and S Donor Atoms

Abstract: Two new heterocyclic Schiff bases of 4-amino-5-mercapto-3-H/propyl-1,2,4-triazole and 5-nitrofurfuraldehyde [HL1-2] and their cobalt, nickel, copper, and zinc complexes have been synthesized and characterized by elemental analyses, spectral (UV-Vis, IR, 1H NMR, Fluorescence, and ESR) studies, thermal techniques, and magnetic moment measurements. The heterocyclic Schiff bases act as bidentate ligands and coordinate with metal ions through nitrogen and sulphur of the thiol group. The low molar conductance values… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 34 publications
1
7
0
Order By: Relevance
“…The decrease in the fluorescence intensity also indicates that the Co(II) ions have a quality of fluorescent quenching. The results of our study are consistent with works reports of Singh et al 35…”
Section: Fluorescence Spectrasupporting
confidence: 94%
“…The decrease in the fluorescence intensity also indicates that the Co(II) ions have a quality of fluorescent quenching. The results of our study are consistent with works reports of Singh et al 35…”
Section: Fluorescence Spectrasupporting
confidence: 94%
“…In the IR spectra of the metal complexes, it was observed that NH 2 group bands were shifted their position indicating binding of NH 2 group with the vanadium metal ion. The characteristic band for υ(SH) was not shown in the spectra of the vanadium (V) complexes suggested deprotonation and hence binding to the vanadium ion through S-atom [36,37].…”
Section: Ir Spectramentioning
confidence: 99%
“…In the spectra of complexes, a shift of electron density from the ligand to metal had been observed. groups and a singlet at 3.32-3.59 and 3.13-3.81 ppm was due to (-CH 2 ) groups [9][10] [11]. S cm − 1 mol − 1 for the Cu(II), Zn(II) and Cd(II) complexes, respectively, indicating their non -electrolytic nature [12].…”
Section: H Nmr Spectramentioning
confidence: 99%